A new look at analytical views on the concept of law in the constitutional era - Hadi Tahan Nazif; Reza Ehsani (پژوهش‌نامه حقوق اسلامی, 2017)
The law is the main center of modern legal system. Iranians were acquainted with the law in constitutional era. Entering this concept in iran created different views. The ideas created range of views, which For his part cause actual events in the Constitutional Revolution and the writing of the constitution. In fact, this views about modernity. This opinions effected on writing Qajar constitution . This developer comments are divided into three categories: progressive, eclectic and against modernity. The first group wanted western law, the second group also wanted western law and islamic jurisprudence and the third group opposed to Western law and only wanted Islamic law. Understanding the law leads to a deeper knowledge of the identity of the Iranian legal system. Also, any talk about rule of law and legislation after reaching a clear idea of the law will occur.This research was performed with descriptive and historical approach.Key words: The concept of law, Modern legal system, constitutionalism, Iranian legal history